Laparoscopic reversal of Hartmann's procedure - Park, Joong-Min (The Korean Surgical Society, 2012)
Reversal of Hartmann's procedure is a major surgical procedure associated with significant morbidity and mortality. Because of the difficulty of the procedure, laparoscopic reversal of Hartmann's procedure is not well established. We describe our experience with this laparoscopic procedure to assess its difficulty and safety. Five patients (4 men and 1 woman) underwent laparoscopic reversal of Hartmann's procedure (LRHP). The initial surgeries were performed to manage obstructive colorectal cancer for 4 patients, and rectovesical fistula for one patient. The procedure was laparoscopically completed for 4 patients. Conversion to open laparotomy was required for one patient, secondary to massive adhesion in lower abdomen. Transient ileostomies were made in 2 cases. Operative time ranged from 240 to 545 minutes. There was no operative mortality. LRHP can be performed safely by an experienced surgeon. However, it is still technically challenging and time consuming.